In vitro rumen fermentation and effect of protein fractions of canola meals on methane production (Scientia Agricola, 2018)
Canola provides oil for human consumption and a by-product from the extraction of its oil canola meal (CM), is used as a good quality protein and lipid supplement for ruminants. The aim of this study was to determine the chemical composition and fermentation profile associated with the potential for methane production of three types of CM: solvent-extracted CM of Brassica napus (CMBN), B. juncea (CMBJ) and cold press-extracted CM from B. napus (CPCM) used to feed ruminants. The protein content of canola meal ranged from 36 to 41 %. The acid and neutral detergent insoluble in nitrogen ranged from 1 to 2 % and 4 to 5 %, respectively. The lipid content of canola meal samples ranged from 2 % (CMBN, CMBJ) to 14 % (CPCM). In vitro, dry matter disappearance of CMBJ was higher than that of other types of CM at 4 h, 24 h and 48 h. Gas production from CMBJ was greater than that of CPCM and CMBN at 24 h and 48 h of incubation. CPCM produced lower methane than CMBJ at 48 h of incubation. CPCM produced a higher (p < 0.05) molar proportion of propionate from 12 h to 48 h of incubation. In conclusion, this study found that CPCM could be a good source of protein (mainly PB2) and lipids in the feed of ruminants; it will decrease methane production and enhance propionate production. There was correlation between less methane production, and the content of lipids and PB2 in the three types of CM studied.